Longitudinal and abattoir-based surveillance of MERS-CoV in camels in Jordan, 2018–2020 - Mustafa M. Ababneh; Shawkat Q. Lafi; Sameeh M. Abutarbush; Mohamad S. Khalifeh; Zaidoun S.K. Hijazeen; Wafaa A. Ramadneh; Maisa S. Al Ameer; Fadia Y. Abukhalifeh; Tamam A. Kutkut; Rachel A. Dodeen; Ihab El Masry; Sophie von Dobschuetz (Heliyon, 2021)
To generate baseline information to help better understand the antibody kinetics and nasal shedding dynamics of MERS-CoV in camels in Jordan, a longitudinal surveillance study was conducted in two phases; phase 1 was between December, 2018 and January, 2019 and phase 2 between August and December 2020. In each phase, two camel herds were studied. These herds were located in Al-azraq and in Al-ramtha area and were named Al-azraq and Al-ramtha herds, respectively. The same camel herd of Al-zarqa area was sampled in both phases while two different camel herds, one in each phase, were sampled in Al-ramtha area. Blood and nasal swabs were collected from same selected animals in all visits to each herd in both phases. Additionally, nasal swabs and retropharyngeal lymph node tissue samples were collected from sixty-one camels slaughtered at Al-ramtha abattoir during phase 2 to enhance virus isolation opportunities and phylogenetic analysis. All sampled animals from Al-azraq camel herd were either borderline or seropositive on spike 1 based ELISA assay and negative on quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) in both phases. In Al-ramtha camel herds, an unsteady pattern prevailed in animals’ seropositivity in both phases and viral RNA was detected in all animals in the end of phase 1 and in one animal during phase 2. For the seroconversion, anti-MERS-CoV spike 1 antibodies were detected in two animals in phase 1 in the first collection only. While, in phase 2, intermittent seroconversion pattern was observed in several samples over time of collections that ended with all animals became seropositive in the last collection (after nineteen days from viral RNA detection). In addition, viral RNA was detected in nasal swabs of 3 slaughtered camels. Phylogenetic analysis of a partial fragment of spike 1 gene sequences of all MERS-CoV isolates clustered together with clade B of MERS-CoV. This cluster contains all MERS-CoV sequences obtained either from camels or human sources in the Arabian Peninsula indicating the continuous circulation of this clade also in Jordan.